ASSESSING KEY TECHNOLOGY FOR FACILITIES MANAGEMENT IN MALAYSIA - Abu Bakar, Zulazhan; Kamaruzzaman, Syahrul Nizam (Journal of Surveying, Construction and Property, 2023)
The Facilities Management (FM) industry is seeing expansion and growth in Malaysia; nevertheless for the industry to elevate to a new level of success, it must overcome various technological barriers that have slowed its adoption of technology. The purpose of this research is to gain an understanding of the key technologies that the Malaysian market is prioritising and, consequently, to determine whether the industry is keeping pace with technological advancement. This study analysed the significance of ten (10) essential FM technologies and five (5) deployment FM areas with specific focus on real estate and commercial property sector in FM. The research employed purposive sampling to assemble an expert panel, and then used a questionnaire with a five-point Likert scale to conduct a Delphi study to evaluate the relative importance of each technology and implementation area. Each member of the expert panel was interviewed separately, and the survey was distributed to each of them. According to the findings, CMMS is identified as the technology with the most significant function as data and information management, and maintenance and operations management, whereas BAS is a significant technology for energy management. In conclusion, the research demonstrated that technology adoption in Malaysia is concentrated on legacy technology, hence emerging technology has not yet been considered due to factors such as untested use case, high risk on return on investment, the complexity of new technology and lack of organisational support. The implication of this study shows that adoption is still in its infancy stage; consequently, additional awareness, collaboration between academia and industry, investment in training, and prospects for industry efficiency and productivity are required. While the focus of the research is confined to real estate and commercial property, additional research can be conducted on other segments of the FM industry in Malaysia, including healthcare and education.